2008
DOI: 10.1007/s12111-008-9038-5
|View full text |Cite
|
Sign up to set email alerts
|

Private Regard, Identity Protection and Perceived Racism among African American Males

Abstract: Previous research has documented the negative effects of racism on the psychological health of African American males. However, consideration of racial identity as a potential buffer against racist experiences has received limited attention. This analysis investigates whether one dimension of the Multidimensional Model of Racial Identity, private regard, reduces the effect of racism on internalizing symptoms in 107 African American late-adolescent males. Findings show that racist experiences were positively as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
57
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(66 citation statements)
references
References 43 publications
7
57
2
Order By: Relevance
“…9,45,49,67-71 Compared with other groups, Asian youth report higher levels of personal racism from peers (eg, racial slurs and name calling, rejection, physical harm threats, and exclusion from peer activities). 67,70 Black girls are more likely than other girls to report exposure to racism, and black males and females experience steep increases in racial discrimination as they grow older, especially from adults in positions of authority such as police officers. [71][72][73][74][75][76][77][78] …”
Section: Exposure To Racial Discriminationmentioning
confidence: 99%
See 3 more Smart Citations
“…9,45,49,67-71 Compared with other groups, Asian youth report higher levels of personal racism from peers (eg, racial slurs and name calling, rejection, physical harm threats, and exclusion from peer activities). 67,70 Black girls are more likely than other girls to report exposure to racism, and black males and females experience steep increases in racial discrimination as they grow older, especially from adults in positions of authority such as police officers. [71][72][73][74][75][76][77][78] …”
Section: Exposure To Racial Discriminationmentioning
confidence: 99%
“…10,11,61,70,79,80 Many become hypervigilant in an effort to detect racial discrimination and adjust their behavior to reduce the chance of racially aversive interactions. 80 Children of color aged 3 to 4 years are most likely to identify with members of dominant social groups and negative racial stereotypes.…”
Section: Development Of Racial Awarenessmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Greene et al (2006) found that a sense of pride and belonging in one's ethnic group protected ethnic minority youths' self-esteem from the negative impacts of ethnic discrimination. Similarly, Bynum, Best, Barnes, and Burton (2008) found that African American youth who experienced discrimination but reported higher levels of private regard were less likely to report anxiety symptoms. Rivas-Drake et al (2008) also found that higher levels of private regard protected African American youth from the exacerbating effects of discrimination on depressive symptoms, although this moderating effect was not observed among Chinese American students.…”
Section: The Moderating Role Of Private Regard and Public Regardmentioning
confidence: 91%